Experimental and simulation study of a diffuser augmented wind turbine to enhance the performance by modifying diffuser and rotor - Jabbar, Balasem Abdulameer (2019)
Wind energy technology represented in wind turbines is one of the fastest growing alternative energy technologies, especially horizontal axis wind turbine (HAWT) type which is more efficient, compared to other conventional wind turbines. However, it is less utilized in urban areas due to the relatively low wind velocity in these areas. In the this work, a technique of augmenting wind by the concept of diffuser augmented wind turbine (DAWT) has been presented to improve the efficiency of small scale of HAWT by enclosing it with a suitable diffuser. The study included two stages for performance improvement; first, developing the diffuser design in three configurations, and second, developing the design of HAWT rotor blades based on the maximum increase of wind velocity in the modified diffuser; at the rotor position, a Modified Theory was used. Two models of DAWT were obtained; one of them was installed with the preliminary rotor, while the other one was installed with the modified rotor where aerodynamic performance predictions of the diffuser, bare HAWT, and DAWTs models have been studied through experimental and simulation approaches. The simulation study was performed using 3-D CFD models based on the SST k-ω turbulence model using ANSYS 19.1, while the experimental study was conducted in an open-loop wind tunnel. The performance evaluations of the models were established in terms of power, torque and aerodynamics coefficient which were power coefficient and torque coefficient. The systematic analysis of these quantities showed that DAWT with a flanged diffuser achieved a significant increase in performance compared to bare HAWT. The results also demonstrated that DAWT with flange angle of 0˚, at both rotors models, achieved the best augmented in power, compared to other flange configurations. On the other hand, the average power was augmented in the DAWT at 0˚flange angle (ϴf) with the preliminary rotor (FDAWT-PR) by around 256%, compared to bare HAWT, while the augmentation reached up to 291% in DAWT with the modified rotor (FDAWT-MR) at same flange angle. In addition, FDAWT (ϴf =0˚)-MR has a simple shape, economic, and compact size. Furthermore, the simulation was conducted to visualize the fluid flowing around the chosen models, as well as giving precise details that difficult to obtaining them practically.